High-rate charge-discharge lithium iron phosphate battery and preparation method thereof

By accurately controlling the preparation process and composition of the electrode material, using modified conductive agents and optimized electrolyte formulas, combined with winding technology and ultrasonic welding technology, the insufficient performance of lithium iron phosphate batteries under high-rate charging and discharging conditions is solved, and the battery performance with high energy density, high-rate charging and discharging capabilities and good high-temperature stability is achieved.

CN118888864BActive Publication Date: 2025-04-22WUHU CHURUI INTELLIGENT TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410934338.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-04-22
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The existing lithium iron phosphate batteries have insufficient performance under high-rate charging and discharge conditions, and their capacity retention and cycle stability have significantly decreased.

Method used

By precisely controlling the preparation process and composition of the electrode material, using modified conductive agents and optimized electrolyte formulations, combined with winding technology and ultrasonic welding technology, a compact and secure connection battery cell is built.

Benefits of technology

It significantly improves the battery's high-rate charging and discharging capacity, cycle stability and structural integrity, extends the battery's service life, and improves the battery's energy density and electrochemical performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high-rate charge-discharge lithium iron phosphate battery and a preparation method thereof, which belongs to the technical field of lithium battery production, and comprises the following steps: constructing a positive electrode sheet, preparing a negative electrode sheet, using a winding technology to wind the positive electrode sheet, the negative electrode sheet and a PE ceramic diaphragm to form a battery core, encapsulating it in an aluminum-plastic film and baking it; finally, injecting an electrolyte prepared by lithium hexafluorophosphate and an electrolyte solvent, and baking it to ensure sufficient infiltration. Compared with the prior art, the lithium iron phosphate battery prepared by this method exhibits excellent high-rate charge-discharge performance and long-term cycle stability, and is suitable for applications requiring high-performance batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery production, and in particular to a high-rate charge-discharge lithium iron phosphate battery and a preparation method thereof. Background Art

[0002] With the rapid development of portable electronic devices, electric vehicles and large-scale energy storage systems, the demand for high-performance batteries is growing. Lithium-ion batteries have become the mainstream choice in the current market due to their high energy density, long cycle life and good environmental adaptability. In particular, lithium iron phosphate batteries are widely used in the above fields due to their high safety, long cycle life and cost-effectiveness.

[0003] However, existing lithium iron phosphate batteries have certain limitations in high-rate charge and discharge performance. Under high-rate charge and discharge conditions, the battery's capacity retention and cycle stability tend to drop significantly, mainly due to factors such as insufficient conductivity of the electrode material, poor wettability of the electrolyte, and insufficient stability of the battery structure.

[0004] In order to solve these problems, researchers have conducted a lot of research work, including developing new electrode materials, improving battery structure design, optimizing electrolyte formulations, and adopting advanced battery manufacturing processes. Among them, improving the conductivity of electrode materials is the key to improving high-rate charge and discharge performance. The traditional approach is to add conductive agents, such as carbon nanotubes and graphene, but these materials often have problems such as poor dispersibility and insufficient bonding with electrode active substances.

[0005] In addition, the battery manufacturing process also has a decisive influence on the performance of the final product. The battery winding, welding, packaging and other process steps need to be precisely controlled to ensure the stability of the battery structure and the consistency of electrochemical performance. However, the existing manufacturing process still needs to be optimized in achieving high-rate charge and discharge performance.

[0006] China's invention patent CN116259929B discloses a high-performance lithium battery current collector, conductive slurry and its preparation method. The functional coating of the current collector is a functional layered covering structure with a thickness of no more than 800nm ​​formed by coating the conductive slurry on the surface of the metal foil and drying; the functional coating includes a plurality of strip-shaped modified conductive agents, which are parallel to each other in the functional coating after curing and forming, and their axes are arranged obliquely with the surface of the metal foil at an angle of 15 to 45° along the thickness of the coating, and interweave with the modified nanofibers, binders and conductive agents in the coating to form an oriented three-dimensional network connection structure with enhanced fixation, electrical and thermal conductivity, uniform deformation and automatic reset. The functional coating of the invention can automatically adapt and offset the volume, etc., and can maintain the relative stability of the connection network and electrical connection strength during the expansion and contraction of the active material during charge and discharge, thereby improving the comprehensive performance of the lithium battery. However, the high-performance lithium battery current collector prepared by the invention has the problems of complex manufacturing, poor durability and stability under long-term cyclic use. Summary of the invention

[0007] In view of the problem in the prior art that lithium iron phosphate batteries have insufficient performance under high-rate charge and discharge conditions, the present invention provides a lithium iron phosphate battery and a preparation method thereof that achieves high-rate charge and discharge capability, excellent cycle stability and structural integrity by precisely controlling the preparation process and composition of electrode materials and the innovative design of modified conductive agents, thereby significantly improving the comprehensive performance and application range of the battery.

[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0009] A method for preparing a lithium iron phosphate battery with high rate charge and discharge capability is as follows:

[0010] Step 1: Preparation of positive electrode sheet: Mix lithium iron phosphate powder, modified conductive agent and polyvinylidene fluoride in N-methylpyrrolidone and stir for 1 to 3 hours to form a uniform positive electrode slurry. The obtained positive electrode slurry has a gram capacity of 140 to 150 mAh / g and a viscosity of 2 to 2.5 g / cm 2 The compaction density is 8-12 μm thick aluminum foil as a substrate, the positive electrode slurry is evenly coated on it, and then dried, rolled and sheared into 4-8 mm wide strips to form a positive electrode sheet;

[0011] Step 2: Preparation of negative electrode sheet: Mix and stir the copper-impregnated graphite block with conductive carbon black, thickener, SBR emulsion and deionized water under vacuum conditions of -0.08 to -0.1 MPa for 1 to 3 hours to prepare a negative electrode slurry having a gram-specific capacity of 350 to 370 mAh / g and a viscosity of 1.4 to 1.6 g / cm 2The compaction density is 8-12 μm thick copper foil is used as the substrate, the negative electrode slurry is coated and dried, and then rolled and sheared into strips with a width of 4-8 mm to form a negative electrode sheet;

[0012] Step 3, assembling the battery core: winding the positive electrode sheet, the negative electrode sheet and the single-layer PE ceramic separator in sequence to form a battery core, connecting the positive and negative electrode ears by ultrasonic welding technology, and encapsulating the battery core in an aluminum-plastic film, and baking the encapsulated battery core at 80 to 90° C. for 20 to 40 hours in a vacuum environment of -0.6 to -0.9 MPa to obtain a pre-processed battery;

[0013] Step 4, injection of electrolyte: 0.8-1.2 mol / L lithium hexafluorophosphate is selected as the electrolyte, and the electrolyte is prepared with the electrolyte solvent to form an electrolyte, and the electrolyte is injected into the shell of the pre-processed battery. After the injection, it is baked for 8-15 hours in an inert gas atmosphere to ensure that the electrolyte is fully infiltrated to obtain a high-rate charge and discharge lithium iron phosphate battery.

[0014] The weight proportions of the substances in step 1 are 80 to 95 parts of lithium iron phosphate powder, 4 to 8 parts of modified conductive agent, 3 to 5 parts of polyvinylidene fluoride, and 30 to 40 parts of N-methylpyrrolidone.

[0015] The weight proportions of the substances in step 2 are 80-95 parts of copper-impregnated graphite blocks, 1-3 parts of conductive carbon black, 1-2 parts of thickeners, 1-3 parts of SBR emulsions, and 30-50 parts of deionized water.

[0016] The electrolyte solvent is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, methyl vinyl carbonate, and vinylene carbonate.

[0017] The weight proportion of the electrolyte in step 4 is 4 to 8 parts.

[0018] The thickener is sodium carboxymethyl cellulose.

[0019] The preparation method of the modified conductive agent is as follows, in parts by weight:

[0020] S1: Take 4 to 6 parts of multi-walled carbon nanotubes, put them into 700 to 900 parts of a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:3 to 5, and ultrasonically treat them for 4 to 6 hours to uniformly disperse the multi-walled carbon nanotubes in the mixed solution, wherein the concentration of concentrated sulfuric acid is 97 to 98 wt%, and the concentration of concentrated nitric acid is 68 to 69 wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 50 to 70°C for 3 to 5 hours for oxidation, diluted with 1800 to 2200 parts of deionized water, and vacuum filtered through a 0.1 to 0.3 μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 40 to 60°C for 20 to 40 hours, and grind it through a 200 to 300 mesh sieve to obtain pretreated carbon nanotubes;

[0021] S2: adding the pretreated carbon nanotubes, 10 to 15 parts of adipic acid dihydrazide and 4 to 6 parts of N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine to 80 to 120 parts of acetone, ultrasonically treating for 0.5 to 2 hours, adding 0.5 to 2 parts of 1-cyclohexyl-3-(2-N-morpholinylethyl)carbodiimide, mixing evenly, reflux heating at 70 to 80° C. for 20 to 30 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 50 to 70° C. for 25 to 40 hours, grinding through a 200 to 300 mesh sieve to obtain post-treated carbon nanotubes;

[0022] S3: Add 4 to 6 parts of post-treated carbon nanotubes and 3 to 7 parts of nano-conductive agent particles to 120 to 180 parts of organic solvent, ultrasonically disperse for 4 to 6 hours, add 1 to 3 parts of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 70 to 90°C for 15 to 30 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 60 to 80°C for 15 to 25 hours, grind it through a 200 to 300 mesh sieve to obtain a modified conductive agent.

[0023] The organic solvent is at least one of acetone and xylene.

[0024] The nano-conductive agent particles are at least one of conductive carbon black and graphene oxide.

[0025] A lithium iron phosphate battery with high rate charge and discharge capability is prepared by adopting the preparation method.

[0026] In the present invention, the functions of each substance are as follows:

[0027] As the positive electrode material, lithium iron phosphate powder has high theoretical capacity and good cycle stability and is the main source of battery energy storage.

[0028] Modified conductive agents are prepared through specific chemical treatments and are used to improve the conductivity of electrode materials and enhance the electrochemical reaction between electrodes and electrolytes, thereby improving the charge and discharge efficiency and cycle stability of batteries.

[0029] Polyvinylidene fluoride acts as a binder for the positive electrode sheet, helping to adhere the active material, conductive agent and aluminum foil substrate together to maintain the integrity of the electrode structure.

[0030] N-methylpyrrolidone is used as a solvent to dissolve polyvinylidene fluoride and other solid substances to form a uniform positive electrode slurry for easy coating and drying.

[0031] Copper-impregnated graphite block is used as negative electrode material. Copper-impregnated graphite has high theoretical capacity and good conductivity, and is the main place for the insertion and extraction of lithium ions during the charging and discharging process of the battery.

[0032] Conductive carbon black improves the conductivity in the negative electrode and ensures the electron transport inside the negative electrode material.

[0033] Sodium carboxymethyl cellulose acts as a thickener for the negative electrode slurry, helping the negative electrode material to adhere to the copper foil substrate and maintain the stability of the negative electrode structure.

[0034] SBR emulsion acts as a binder for negative electrode slurry, enhancing the adhesion and structural stability of negative electrode materials.

[0035] Deionized water is used as a solvent for the negative electrode slurry and is mixed with sodium carboxymethyl cellulose and SBR emulsion to form a uniform negative electrode slurry.

[0036] Copper foil and aluminum foil serve as the base materials for the negative electrode and positive electrode, respectively, providing good conductivity and mechanical support.

[0037] The single-layer PE ceramic separator isolates the positive and negative electrodes in the battery core to prevent short circuits, while allowing lithium ions to pass through to complete the charging and discharging process.

[0038] Lithium hexafluorophosphate serves as an electrolyte in the electrolyte, providing lithium ions and ensuring ion transport within the battery.

[0039] As a solvent for the electrolyte, ethylene carbonate dissolves the electrolyte and forms a stable electrolyte, thus ensuring the electrochemical performance of the battery.

[0040] 1-cyclohexyl-3-(2-N-morpholinylethyl) carbodiimide promotes the chemical bonding between carbon nanotubes and other substances during the preparation process of the modified conductive agent, thereby improving the performance of the conductive agent.

[0041] Multi-walled carbon nanotubes, as the main component of modified conductive agents, have better dispersibility and conductivity after chemical treatment.

[0042] Substances such as adipic acid dihydrazide and N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine are used as part of the modified conductive agent and are combined with carbon nanotubes through chemical reactions to improve the functionality of the conductive agent.

[0043] The synergistic effect of these substances ensures the battery's high energy density, high-rate charge and discharge capability, and good cycle stability.

[0044] Compared with the prior art, it has the following beneficial effects:

[0045] 1) The present invention enhances the conductivity of the electrode material by using a specific modified conductive agent, thereby improving the performance of the battery under high-rate charge and discharge conditions and the cycle stability of the battery under high-temperature conditions, thereby extending the service life of the battery.

[0046] 2) The present invention adopts winding technology and ultrasonic welding technology to improve the structural stability of the battery core and reduce the possibility of electrode material shedding or structural damage during the charging and discharging process.

[0047] 3) The present invention improves the gram-specific capacity and compaction density of the electrode material by optimizing the formula and preparation process of the positive and negative electrode slurries, thereby increasing the energy density of the battery.

[0048] 4) The present invention selects an electrolyte formula suitable for high-rate charge and discharge, and performs sufficient baking after injection to ensure uniform infiltration of the electrolyte in the battery and improve the electrochemical performance of the battery. DETAILED DESCRIPTION

[0049] Main sources of substances:

[0050] PE ceramic diaphragm: Shenzhen Yuanchenghui Electronics Co., Ltd., model: 12+4um.

[0051] Lithium iron phosphate powder: Shenzhen Liyou New Energy Technology Co., Ltd., molecular formula: LiFePO4, bulk density: ≥0.30g / cm 3 Specific surface area: 10.0±1.5m 2 / g, tap density: ≥0.80 / cm 3 , water content: ≤500ug / g.

[0052] Polyvinylidene fluoride: Dongguan Ruiqian New Materials Co., Ltd., brand: 740.

[0053] Copper impregnated graphite block: Xinxiang Xinshan Technology Co., Ltd., item number: xs240304.

[0054] Conductive carbon black: Tianjin Tianyi Century Chemical Products Technology Development Co., Ltd., item number: KBT1.

[0055] Sodium carboxymethyl cellulose: Hebei Yanxing Chemical Co., Ltd., product number: 201cmc.

[0056] SBR emulsion: Waidian International Chemical Store, brand: AL-3001A.

[0057] Multi-walled carbon nanotubes: Jiaxing Bona New Materials Co., Ltd., model: NACODC8.

[0058] N-[3-[Tri(octyloxy)silyl]propyl]ethylenediamine: CAS number: 93804-22-9.

[0059] Adipic acid dihydrazide: CAS number: 1071-93-8.

[0060] 1-Cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide: CAS number: 15580-20-8.

[0061] 3-(4-Ureamido)propyltriethoxysilane: CAS number: 106868-88-6.

[0062] Ureapropyltriethoxysilane: CAS: 23779-32-0.

[0063] Graphene oxide: Jiangxi Shuobang New Material Technology Co., Ltd., model: 188.

[0064] The design idea of ​​the present invention is to achieve a comprehensive improvement in the performance of lithium iron phosphate batteries by comprehensively considering the chemical composition, physical structure and battery manufacturing process of the electrode materials. First, through specific chemical pretreatment and post-treatment steps, a modified conductive agent with enhanced conductivity and dispersibility is prepared to improve the electrochemical properties of the electrode material; secondly, the formula and preparation process of the positive and negative electrode slurries are optimized to ensure that the electrodes have high gram-to-weight capacity and suitable compaction density, thereby improving the energy density of the battery; then, winding technology and ultrasonic welding technology are used to construct a battery core with a compact structure and firm connection, thereby improving the assembly efficiency and reliability of the battery; in addition, an electrolyte formula suitable for high-rate charge and discharge is selected, and it is fully baked after injection to ensure uniform infiltration of the electrolyte in the battery; finally, through battery rate testing and high-temperature cycle retention rate testing, the performance of the battery under different conditions is comprehensively evaluated to ensure that the battery can maintain excellent performance and stability under high-rate charge and discharge and high-temperature environments. Through this series of innovative designs, the present invention aims to develop lithium iron phosphate batteries with high energy density, high-rate charge and discharge capabilities and good high-temperature stability to meet the market demand for high-performance battery applications.

[0065] Example 1

[0066] A method for preparing a lithium iron phosphate battery with high rate charge and discharge capability is as follows:

[0067] Step 1: Construction of positive electrode sheet: 90g lithium iron phosphate powder, 6g modified conductive agent and 4g polyvinylidene fluoride were mixed in 35g N-methylpyrrolidone solvent and stirred for 2 hours to form a uniform positive electrode slurry. The obtained positive electrode slurry had a gram specific capacity of 145mAh / g and a viscosity of 2.3g / cm 2 The compaction density is 10 μm thick aluminum foil as the substrate, the positive electrode slurry is evenly coated on it, and then dried, rolled and cut into 6 mm wide strips to form a positive electrode sheet;

[0068] Step 2: Preparation of negative electrode sheet: 92g copper-impregnated graphite block, 2g conductive carbon black, 1.2g sodium carboxymethyl cellulose, 2g SBR emulsion and 40g deionized water were mixed and stirred for 2 hours under a vacuum condition of -0.09MPa to prepare a negative electrode slurry. The negative electrode slurry had a gram-specific capacity of 360mAh / g and a specific capacity of 1.5g / cm 2 The compaction density is 10 μm; a copper foil with a thickness of 10 μm is used as the substrate, coated with the negative electrode slurry and dried, and then rolled and cut into strips with a width of 6 mm to form a negative electrode sheet;

[0069] Step 3, assembly of battery core: winding the positive electrode sheet, the negative electrode sheet and the single-layer PE ceramic separator in sequence to form a battery core, connecting the positive and negative electrode ears by ultrasonic welding technology, and encapsulating the battery core in an aluminum-plastic film, and baking the encapsulated battery core at 90°C for 30 hours in a vacuum environment of -0.8MPa to obtain a pre-processed battery;

[0070] Step 4, injection of electrolyte: 1.0 mol / L lithium hexafluorophosphate is selected as the electrolyte and ethylene carbonate is used as the solvent. 6 g of electrolyte is injected into the shell of the pre-processed battery. After injection, it is baked for 12 hours in an inert gas atmosphere to ensure that the electrolyte is fully infiltrated to obtain a high-rate charge and discharge lithium iron phosphate battery.

[0071] The preparation method of the modified conductive agent is as follows:

[0072] S1: Take 5g of multi-walled carbon nanotubes, put them into 800g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:4, and ultrasonically treat them for 5 hours to make the multi-walled carbon nanotubes evenly dispersed in the mixed solution, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of concentrated nitric acid is 68wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 60°C for 4 hours for oxidation, diluted with 2kg of deionized water, and vacuum filtered through a 0.2μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 50°C for 32 hours, and grind it through a 300-mesh sieve to obtain pretreated carbon nanotubes;

[0073] S2: adding the pretreated carbon nanotubes, 12 g of adipic acid dihydrazide and 5 g of N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine to 100 g of acetone, ultrasonically treating for 1 hour, adding 1 g of 1-cyclohexyl-3-(2-N-morpholinylethyl)carbodiimide, mixing evenly, reflux heating at 75° C. for 24 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 60° C. for 30 hours, grinding through a 300-mesh sieve to obtain post-treated carbon nanotubes;

[0074] S3: Add 5 g of post-treated carbon nanotubes, 3 g of conductive carbon black and 2 g of graphene oxide to 150 g of acetone, ultrasonically disperse for 5 hours, add 2 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 80°C for 20 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 70°C for 20 hours, grind it through a 300-mesh sieve to obtain a modified conductive agent.

[0075] Example 2

[0076] The preparation method of a lithium iron phosphate battery with high rate charge and discharge capability is basically the same as that of Example 1, the only difference being that the preparation method of the modified conductive agent is different.

[0077] The preparation method of the modified conductive agent is as follows:

[0078] S1: Take 5g of multi-walled carbon nanotubes, put them into 800g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:4, and ultrasonically treat them for 5 hours to make the multi-walled carbon nanotubes evenly dispersed in the mixed solution, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of concentrated nitric acid is 68wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 60°C for 4 hours for oxidation, diluted with 2kg of deionized water, and vacuum filtered through a 0.2μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 50°C for 32 hours, and grind it through a 300-mesh sieve to obtain pretreated carbon nanotubes;

[0079] S2: pretreated carbon nanotubes, 12 g 1,4-cyclohexanebis(methylamine) and 5 g N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine were added to 100 g acetone, and ultrasonically treated for 1 hour. 1 g 1-cyclohexyl-3-(2-N-morpholinylethyl)carbodiimide was added, mixed evenly, refluxed at 75° C. for 24 hours, and excess reaction by-products were ultrasonically washed away with anhydrous ethanol. The mixture was filtered and washed again, and the solid on the filter membrane was collected. The solid was then dried in a vacuum drying oven at 60° C. for 30 hours, and ground through a 300-mesh sieve to obtain post-treated carbon nanotubes.

[0080] S3: Add 5 g of post-treated carbon nanotubes, 3 g of conductive carbon black and 2 g of graphene oxide to 150 g of acetone, ultrasonically disperse for 5 hours, add 2 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 80°C for 20 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 70°C for 20 hours, grind it through a 300-mesh sieve to obtain a modified conductive agent.

[0081] Example 3

[0082] The preparation method of a lithium iron phosphate battery with high rate charge and discharge capability is basically the same as that of Example 1, the only difference being that the preparation method of the modified conductive agent is different.

[0083] The preparation method of the modified conductive agent is as follows:

[0084] S1: Take 5g of multi-walled carbon nanotubes, put them into 800g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:4, and ultrasonically treat them for 5 hours to make the multi-walled carbon nanotubes evenly dispersed in the mixed solution, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of concentrated nitric acid is 68wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 60°C for 4 hours for oxidation, diluted with 2kg of deionized water, and vacuum filtered through a 0.2μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 50°C for 32 hours, and grind it through a 300-mesh sieve to obtain pretreated carbon nanotubes;

[0085] S2: adding the pretreated carbon nanotubes, 12 g of 1,6-hexanediamine and 5 g of N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine to 100 g of acetone, ultrasonically treating for 1 hour, adding 1 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, mixing evenly, reflux heating at 75° C. for 24 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 60° C. for 30 hours, grinding through a 300-mesh sieve to obtain post-treated carbon nanotubes;

[0086] S3: Add 5 g of post-treated carbon nanotubes, 3 g of conductive carbon black and 2 g of graphene oxide to 150 g of acetone, ultrasonically disperse for 5 hours, add 2 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 80°C for 20 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 70°C for 20 hours, grind it through a 300-mesh sieve to obtain a modified conductive agent.

[0087] Example 4

[0088] The preparation method of a lithium iron phosphate battery with high rate charge and discharge capability is basically the same as that of Example 1, the only difference being that the preparation method of the modified conductive agent is different.

[0089] The preparation method of the modified conductive agent is as follows:

[0090] S1: Take 5g of multi-walled carbon nanotubes, put them into 800g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:4, and ultrasonically treat them for 5 hours to make the multi-walled carbon nanotubes evenly dispersed in the mixed solution, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of concentrated nitric acid is 68wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 60°C for 4 hours for oxidation, diluted with 2kg of deionized water, and vacuum filtered through a 0.2μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 50°C for 32 hours, and grind it through a 300-mesh sieve to obtain pretreated carbon nanotubes;

[0091] S2: adding the pretreated carbon nanotubes, 12 g of adipic acid dihydrazide and 5 g of ureapropyltriethoxysilane to 100 g of acetone, ultrasonically treating for 1 hour, adding 1 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, mixing evenly, reflux heating at 75° C. for 24 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 60° C. for 30 hours, grinding through a 300-mesh sieve to obtain post-treated carbon nanotubes;

[0092] S3: Add 5 g of post-treated carbon nanotubes, 3 g of conductive carbon black and 2 g of graphene oxide to 150 g of acetone, ultrasonically disperse for 5 hours, add 2 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 80°C for 20 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 70°C for 20 hours, grind it through a 300-mesh sieve to obtain a modified conductive agent.

[0093] Example 5

[0094] The preparation method of a lithium iron phosphate battery with high rate charge and discharge capability is basically the same as that of Example 1, the only difference being that the preparation method of the modified conductive agent is different.

[0095] The preparation method of the modified conductive agent is as follows:

[0096] S1: Take 5g of multi-walled carbon nanotubes, put them into 800g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:4, and ultrasonically treat them for 5 hours to make the multi-walled carbon nanotubes evenly dispersed in the mixed solution, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of concentrated nitric acid is 68wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 60°C for 4 hours for oxidation, diluted with 2kg of deionized water, and vacuum filtered through a 0.2μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 50°C for 32 hours, and grind it through a 300-mesh sieve to obtain pretreated carbon nanotubes;

[0097] S2: adding the pretreated carbon nanotubes, 12 g of adipic acid dihydrazide and 5 g of 3-(4-ureaamino)propyltriethoxysilane to 100 g of acetone, ultrasonically treating for 1 hour, adding 1 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, mixing evenly, reflux heating at 75° C. for 24 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 60° C. for 30 hours, grinding through a 300-mesh sieve to obtain post-treated carbon nanotubes;

[0098] S3: Add 5 g of post-treated carbon nanotubes, 3 g of conductive carbon black and 2 g of graphene oxide to 150 g of acetone, ultrasonically disperse for 5 hours, add 2 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 80°C for 20 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 70°C for 20 hours, grind it through a 300-mesh sieve to obtain a modified conductive agent.

[0099] Example 6

[0100] The preparation method of a lithium iron phosphate battery with high rate charge and discharge capability is basically the same as that of Example 1, the only difference being that the preparation method of the modified conductive agent is different.

[0101] The preparation method of the modified conductive agent is as follows:

[0102] S1: Take 5g of multi-walled carbon nanotubes, put them into 800g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:4, and ultrasonically treat them for 5 hours to make the multi-walled carbon nanotubes evenly dispersed in the mixed solution, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of concentrated nitric acid is 68wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 60°C for 4 hours for oxidation, diluted with 2kg of deionized water, and vacuum filtered through a 0.2μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 50°C for 32 hours, and grind it through a 300-mesh sieve to obtain pretreated carbon nanotubes;

[0103] S2: adding the pretreated carbon nanotubes, 12 g of adipic acid dihydrazide and 5 g of 3-aminopropyltriethoxysilane to 100 g of acetone, ultrasonically treating for 1 hour, adding 1 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, mixing evenly, reflux heating at 75° C. for 24 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 60° C. for 30 hours, grinding through a 300-mesh sieve to obtain post-treated carbon nanotubes;

[0104] S3: Add 5 g of post-treated carbon nanotubes, 3 g of conductive carbon black and 2 g of graphene oxide to 150 g of acetone, ultrasonically disperse for 5 hours, add 2 g of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux at 80°C for 20 hours, ultrasonically wash away excess by-products with anhydrous ethanol, filter and wash, collect the solid on the filter membrane, and then dry it in a vacuum drying oven at 70°C for 20 hours, grind it through a 300-mesh sieve to obtain a modified conductive agent.

[0105] Comparative Example 1

[0106] A method for preparing a lithium iron phosphate battery with high rate charge and discharge capability is as follows:

[0107] Step 1: Construction of positive electrode sheet: 90g lithium iron phosphate powder, 6g conductive agent and 4g polyvinylidene fluoride were mixed in 35g N-methylpyrrolidone solvent and stirred for 2 hours to form a uniform positive electrode slurry. The conductive agent was composed of multi-walled carbon nanotubes, conductive carbon black and graphene oxide in a mass ratio of 5:3:2. The obtained positive electrode slurry had a gram-specific capacity of 145mAh / g and a viscosity of 2.3g / cm 2 The compaction density is 10 μm thick aluminum foil as the substrate, the positive electrode slurry is evenly coated on it, and then dried, rolled and cut into 6 mm wide strips to form a positive electrode sheet;

[0108] Step 2: Preparation of negative electrode sheet: 92g copper-impregnated graphite block, 2g conductive carbon black, 1.2g sodium carboxymethyl cellulose, 2g SBR emulsion and 40g deionized water were mixed and stirred for 2 hours under a vacuum condition of -0.09MPa to prepare a negative electrode slurry. The negative electrode slurry had a gram-specific capacity of 360mAh / g and a specific capacity of 1.5g / cm 2 The compaction density is 10 μm; a copper foil with a thickness of 10 μm is used as the substrate, coated with the negative electrode slurry and dried, and then rolled and cut into strips with a width of 6 mm to form a negative electrode sheet;

[0109] Step 3, assembly of battery core: winding the positive electrode sheet, the negative electrode sheet and the single-layer PE ceramic separator in sequence to form a battery core, connecting the positive and negative electrode ears by ultrasonic welding technology, and encapsulating the battery core in an aluminum-plastic film, and baking the encapsulated battery core at 90°C for 30 hours in a vacuum environment of -0.8MPa to obtain a pre-processed battery;

[0110] Step 4, injection of electrolyte: select 1.0 mol / L lithium hexafluorophosphate as electrolyte and ethylene carbonate as solvent, inject 6g electrolyte into the shell of the pre-processed battery, and after injection, bake for 12 hours in an inert gas atmosphere to ensure that the electrolyte is fully infiltrated to obtain a high-rate charge and discharge lithium iron phosphate battery.

[0111] Test Example 1

[0112] Battery rate test

[0113] Battery rate test is a method to evaluate the performance of lithium-ion batteries at different discharge rates. The specific test steps are as follows: First, at 25°C, charge the battery to a cutoff voltage of 4.2V at a current density of 1Cn, and then charge at a constant voltage until the current drops to 0.05Cn. Next, discharge to 2.5V at a current density of 1Cn and record the discharge capacity. After that, charge again to 4.2V, and then discharge to 2.5V at a current density of 10Cn, and record the discharge capacity. By calculating the ratio of 10Cn discharge capacity to 1Cn discharge capacity, the discharge rate performance of the battery is obtained. The test results reflect the performance of the battery under high rate conditions and are an important indicator for evaluating the comprehensive performance of the battery. The test results are shown in Table 1.

[0114] Table 1

[0115] Experimental protocol 10Cn discharge rate Example 1 91.58% Example 2 87.82% Example 3 86.77% Example 4 88.64% Example 5 86.79% Example 6 84.75% Comparative Example 1 80.61%

[0116] Test Example 2

[0117] High temperature battery cycle retention test

[0118] The test method for high-temperature battery cycle retention rate is as follows: First, at 25°C, charge the battery to a cut-off voltage of 4.2V at a current density of 0.5Cn, and then continue to charge at a constant voltage of 4.2V until the current drops to 0.05Cn. Subsequently, the battery is placed in a high-temperature environment of 45°C, and a cyclic charge and discharge test is performed at this temperature with a charge and discharge current density of 1Cn, and the voltage range is set between 2.5V and 4.2V. During the test, the capacity of the battery before cycling (D0) and after 1200 cycles (Dn) is recorded. The high-temperature cycle retention rate of the battery is calculated by the following formula:

[0119] Capacity retention after 1200 cycles = Dn / D0×100%

[0120] This indicator reflects the capacity retention of the battery after 1,200 cycles under high temperature conditions and is an important parameter for measuring the high temperature stability of the battery. The test results are shown in Table 2.

[0121] Table 2

[0122] Experimental protocol Capacity retention after 1200 cycles Example 1 98.41% Example 2 96.83% Example 3 94.89% Example 4 96.72% Example 5 95.60% Example 6 94.61% Comparative Example 1 89.68%

[0123] It can be seen from test examples 1 to 2 that the high-rate charge and discharge lithium iron phosphate battery obtained in Example 1 of the present invention has the best battery rate and high-temperature battery cycle retention rate.

[0124] In the preparation process of the modified conductive agent of Examples 1 to 3, although the compounds used respectively (adipic acid dihydrazide, 1,4-cyclohexanebis[methylamine], 1,6-hexanediamine) all belong to organic amines, they have differences in molecular structure and chemical properties, which may be the reason why Example 1 performs better.

[0125] Adipic acid dihydrazide is a binary carbonyl compound, and the carbonyl group in its molecule has a high electronegativity, which may help to improve the interfacial bonding strength with multi-walled carbon nanotubes, thereby enhancing the conductivity and the overall performance of the conductive agent. In addition, the molecular structure of adipic acid dihydrazide may be more conducive to forming a uniform modification layer on the surface of carbon nanotubes, thereby improving the dispersibility of the conductive agent and the compatibility with the matrix material.

[0126] Although 1,4-cyclohexanebis[methylamine] and 1,6-hexanediamine also provide amino groups, their molecular structures may limit the contact area and interaction with carbon nanotubes, thus affecting the performance of the conductive agent. In particular, the two amino groups of 1,4-cyclohexanebis[methylamine] are located at relative positions on the ring, which may lead to steric hindrance and affect its binding with carbon nanotubes. Although 1,6-hexanediamine provides a longer carbon chain, its molecular structure may not be as conducive to the formation of a uniform modification layer as adipic acid dihydrazide.

[0127] In addition, the activity of these compounds in chemical reactions may also affect the performance of the final product. For example, adipic acid dihydrazide may be more likely to participate in cross-linking reactions to form a stable network structure, thereby improving the mechanical strength and electrochemical properties of the modified conductive agent.

[0128] In summary, the molecular characteristics of adipic acid dihydrazide may enable it to more effectively improve the surface properties and overall conductivity of carbon nanotubes during the preparation of modified conductive agents, thereby showing better performance in terms of battery rate and high-temperature cycle retention.

[0129] When analyzing the different performances of the battery between Example 1 and Examples 4 to 6, we need to consider the chemical structure and intermolecular forces. The modified conductive agent used in Example 1 contains N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine, while Examples 4, 5 and 6 use ureapropyltriethoxysilane, 3-(4-ureaamino)propyltriethoxysilane and 3-aminopropyltriethoxysilane, respectively.

[0130] N-[3-[Tri(octyloxy)silyl]propyl]ethylenediamine is a compound containing siloxane groups, which can provide good interfacial compatibility and enhanced chemical stability. Siloxane groups can form strong interactions with electrode materials, which helps to improve the structural stability of the battery. In addition, the introduction of siloxane groups may also help to improve the dispersibility of electrode materials, thereby improving the overall performance of the battery.

[0131] In contrast, although ureapropyl triethoxysilane, 3-(4-ureaamino)propyl triethoxysilane and 3-aminopropyl triethoxysilane also contain siloxane groups, their molecular structures lack the long-chain alkyl groups in N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine, which may affect their dispersibility in electrode materials and their interaction with electrode materials. The presence of urea and amino groups may provide hydrogen bonding, but may not be as strong as the van der Waals force of long-chain alkyl groups, so the battery performance may not be as good as the compounds in Example 1.

[0132] In general, the difference in molecular structure, especially the presence or absence of long-chain alkyl and siloxane groups, may be the main reason why the battery performance of Example 1 is better than that of other examples. These structural features affect the interaction between molecules, which in turn affects the conductivity, structural stability and cycle performance of the battery.

Claims

1. A method for preparing a high-rate charge and discharge lithium iron phosphate battery, characterized in that: Here’s how: Step 1, construction of positive electrode sheet: lithium iron phosphate powder, modified conductive agent and polyvinylidene fluoride are mixed in N-methylpyrrolidone, stirred for 1 to 3 hours to form a uniform positive electrode slurry, the obtained positive electrode slurry has a gram capacity of 140 to 150 mAh / g and a compaction density of 2 to 2.5 g / cm2, and an aluminum foil with a thickness of 8 to 12 μm is used as a substrate, the positive electrode slurry is evenly coated on it, and dried, rolled and sheared into strips with a width of 4 to 8 mm to form a positive electrode sheet; Step 2, preparation of negative electrode sheet: mixing copper-impregnated graphite block with conductive carbon black, thickener, SBR emulsion and deionized water under vacuum conditions of -0.08 to -0.1 MPa for 1 to 3 hours to prepare negative electrode slurry, wherein the negative electrode slurry has a gram-specific capacity of 350 to 370 mAh / g and a compaction density of 1.4 to 1.6 g / cm2; using 8 to 12 μm thick copper foil as a substrate, coating the negative electrode slurry and drying it, and then rolling and shearing it into strips with a width of 4 to 8 mm to form a negative electrode sheet; Step 3, assembling the battery core: winding the positive electrode sheet, the negative electrode sheet and the single-layer PE ceramic separator in sequence to form a battery core, connecting the positive and negative electrode ears by ultrasonic welding technology, and encapsulating the battery core in an aluminum-plastic film, and baking the encapsulated battery core at 80 to 90° C. for 20 to 40 hours in a vacuum environment of -0.6 to -0.9 MPa to obtain a pre-processed battery; Step 4, injection of electrolyte: 0.8-1.2 mol / L lithium hexafluorophosphate is selected as the electrolyte, and the electrolyte is prepared with the electrolyte solvent to form an electrolyte, and the electrolyte is injected into the shell of the pre-processed battery. After the injection, the electrolyte is baked for 8-15 hours in an inert gas atmosphere to ensure that the electrolyte is fully infiltrated to obtain a high-rate charge and discharge lithium iron phosphate battery; The preparation method of the modified conductive agent is as follows, in parts by weight: S1: Take 4 to 6 parts of multi-walled carbon nanotubes, put them into 700 to 900 parts of a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:3 to 5, and ultrasonically treat them for 4 to 6 hours to uniformly disperse the multi-walled carbon nanotubes in the mixed solution, wherein the concentration of concentrated sulfuric acid is 97 to 98 wt%, and the concentration of concentrated nitric acid is 68 to 69 wt%. The mixed solution is placed in a constant temperature magnetic stirrer, stirred at 50 to 70°C for 3 to 5 hours for oxidation, diluted with 1800 to 2200 parts of deionized water, and vacuum filtered through a 0.1 to 0.3 μm filter membrane and a membrane filter, and repeatedly washed and filtered with deionized water until the pH of the filtrate is neutral; collect the solid on the filter membrane, dry it in a vacuum drying oven at 40 to 60°C for 20 to 40 hours, and grind it through a 200 to 300 mesh sieve to obtain pretreated carbon nanotubes; S2: adding the pretreated carbon nanotubes, 10 to 15 parts of adipic acid dihydrazide and 4 to 6 parts of N-[3-[tri(octyloxy)silyl]propyl]ethylenediamine to 80 to 120 parts of acetone, ultrasonically treating for 0.5 to 2 hours, adding 0.5 to 2 parts of 1-cyclohexyl-3-(2-N-morpholinylethyl)carbodiimide, mixing evenly, reflux heating at 70 to 80° C. for 20 to 30 hours, ultrasonically washing away excess reaction byproducts with anhydrous ethanol, filtering and washing again, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 50 to 70° C. for 25 to 40 hours, grinding through a 200 to 300 mesh sieve to obtain post-treated carbon nanotubes; S3: adding 4 to 6 parts of post-treated carbon nanotubes and 3 to 7 parts of nano-conductive agent particles to 120 to 180 parts of organic solvent, ultrasonically dispersing for 4 to 6 hours, adding 1 to 3 parts of 1-cyclohexyl-3-(2-N-morpholinoethyl)carbodiimide, reflux heating at 70 to 90° C. for 15 to 30 hours, ultrasonically washing away excess by-products with anhydrous ethanol, filtering and washing, collecting the solid on the filter membrane, and then drying in a vacuum drying oven at 60 to 80° C. for 15 to 25 hours, grinding through a 200 to 300 mesh sieve to obtain a modified conductive agent; The organic solvent is at least one of acetone and xylene; The nano-conductive agent particles are at least one of conductive carbon black and graphene oxide.

2. The method for preparing a high-rate charge-discharge lithium iron phosphate battery according to claim 1, characterized in that: The weight proportions of the substances in step 1 are 80 to 95 parts of lithium iron phosphate powder, 4 to 8 parts of modified conductive agent, 3 to 5 parts of polyvinylidene fluoride, and 30 to 40 parts of N-methylpyrrolidone.

3. The method for preparing a high-rate charge-discharge lithium iron phosphate battery according to claim 1, characterized in that: The weight proportions of the substances in step 2 are 80-95 parts of copper-impregnated graphite blocks, 1-3 parts of conductive carbon black, 1-2 parts of thickeners, 1-3 parts of SBR emulsions, and 30-50 parts of deionized water.

4. The method for preparing a high-rate charge-discharge lithium iron phosphate battery according to claim 1, characterized in that: The electrolyte solvent is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, methyl vinyl carbonate, and vinylene carbonate.

5. The method for preparing a high-rate charge-discharge lithium iron phosphate battery according to claim 1, characterized in that: The weight proportion of the electrolyte in step 4 is 4 to 8 parts.

6. The method for preparing a high-rate charge-discharge lithium iron phosphate battery according to claim 1 or 3, characterized in that: The thickener is sodium carboxymethyl cellulose.

7. A lithium iron phosphate battery with high rate charge and discharge capability, characterized in that: The preparation method is as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • A high-performance lithium battery current collector, conductive slurry, and its preparation method

    CN116259929B

  • High rate lithium iron phosphate cell and preparation method thereof

    CN102403531A

  • Lithium battery and preparation method thereof

    CN107768733A